Preparation, purification, and identification of novel antioxidant peptides derived from Gracilariopsis lemaneiformis protein hydrolysates - Hu, Xiao; Liu, Jing; Li, Jun; Song, Yuqiong; Chen, Shengjun; Zhou, Shaobo; Yang, Xianqing (Frontiers in Nutrition, 2022)
Gracilariopsis lemaneiformis protein was hydrolyzed by alkaline protease to obtain antioxidant peptides. The enzymatic hydrolysis conditions were optimized by single factor experiment and orthogonal experiment. The results showed that the optimal process parameters were using 2% of alkaline protease, and substrate concentration of 1 g/100 mL and hydrolyzed 2 h at pH 8.0. Gel filtration chromatography and RP-HPLC were used to isolate and purify the antioxidant peptides from the G. lemaneiformis protein hydrolysate (GLPH). Three novel antioxidant peptides were identified as LSPGEL (614.68 Da), VYFDR (698.76 Da) and PGPTY (533.57 Da) by nano-HPLC-MS/MS. The results of ABTS free radical scavenging rate indicated that the PGPTY had the best antioxidant activity (IC50 = 0.24 mg/mL). Moreover, LSPGEL, VYFDR and PGPTY were docked with Keap1, respectively. The molecular docking results showed that the docking energy and inhibition constants of PGPTY were smaller than those of the other two peptides. Finally, the cell viability assay indicated that the antioxidant peptide also had a certain protective effect on H2O2-induced oxidative damage. These results suggested that the antioxidant peptides from GLPH could be used as potential antioxidants.